Broadband energy harvesting using nonlinear 2-DOF configuration - Yang, Yaowen (2013)
Vibration energy harvesting using piezoelectric material has received great research interest in the recent years. To enhance the performance of piezoelectric energy harvesters, one important concern is to increase their operating bandwidth. Various techniques have been proposed for broadband energy harvesting, such as the resonance tuning approach, the frequency up-conversion technique, the multi-modal harvesting and the nonlinear technique. Usually, a nonlinear piezoelectric energy harvester can be easily developed by introducing a magnetic field. Either mono-stable or bi-stable response can be achieved using different magnetic configurations. However, most of the research work for nonlinear piezoelectric energy harvesting has focused on the SDOF cantilever beam. A recently reported linear 2-DOF harvester can achieve two close resonant frequencies with significant power outputs. However, for this linear configuration, although a broader bandwidth can be achieved, there exists a deep valley in-between the two response peaks. The presence of the valley will greatly deteriorate the performance of the energy harvester. To overcome this limitation, a nonlinear 2-DOF piezoelectric energy harvester is proposed in this article. This nonlinear harvester is developed from its linear counterpart by incorporating a magnetic field using a pair of magnets. Experimental parametric study is carried out to investigate the behavior of such harvester. With different configurations, both mono-stable and bi-stable behaviors are observed and studied. An optimal configuration of the nonlinear harvester is thus obtained, which can achieve significantly wider bandwidth than the linear 2-DOF harvester and at the same time overcome its limitation.